Physicians' Perspectives on Presurgical Discussion and Shared Decision-Making in Pediatric Epilepsy Surgery. (April 2022) - Samanta, Debopam; Ostendorf, Adam P; Singh, Rani; Gedela, Satyanarayana; Elumalai, Vimala; Hoyt, Megan Leigh; Perry, M. Scott; Bartolini, Luca; Curran, Geoffrey M
Objective: To qualitatively explore the approach of pediatric epilepsy providers when counseling regarding surgical options for epilepsy, presenting risks and benefits of surgery, overcoming resistance to surgery, and fostering shared decision making with patients and families.Methods: We conducted in-depth interviews with 11 academic clinicians (5- neurologists, 5- epileptologists, 1- neurosurgeon) from a Level 4 pediatric epilepsy center to explore how physicians communicate and pursue surgical decision-making.Results: A blended inductive-deductive analysis revealed three key themes (with subthemes) of presurgical discussions: (1) Candidate selection and initial discussion about epilepsy surgery (neurologists compared to epileptologists, the timing of the discussion, reluctant families) (2) Detailed individualized counseling about epilepsy surgery (shared decision-making [enablers and barriers] and risk-benefit analysis [balancing risks and benefits, statistical benefit estimation, discussion about SUDEP, prognostication about cognitive and behavioral outcomes, risks of surgery]) (3) Tools to improve decision-making (educational interventions for patients and families and provider- and organization-specific interventions).Significance: Presurgical discussions lack uniformity among physicians who treat epilepsy. Despite general interest in collaborative decision-making, experts raised concern about lack of exposure to communication training and clinical tools for optimizing decision-making, a high number of families who do not feel equipped to share the decision making leaving the decision-making entirely to the physician, and paucity of practical resources for individualized risk-benefit counseling. Clinical practice guidelines should be developed to reduce existing practice variations in presurgical counseling. Further consensus is needed about when and how to initiate the conversation about epilepsy surgery, essential components of the discussion, and the utility of various tools to improve the utilization of epilepsy surgery.